Comparative Transcriptome and Metabolome Analysis of Resistant and Susceptible Piper Species Upon Infection by the Oomycete Phytophthora Capsici - Fan, Rui; Tao, Xiao-yuan; Xia, Zhi-qiang; Sim, Soonliang; Hu, Li-song; Wu, Bao-duo; Wang, Qing-huang; Hao, Chao-yun (Frontiers in Plant Science, 2022)
Phytophthora capsici is a destructive oomycete pathogen that causes devastating disease in black pepper, resulting in significant decline in yield and economic losses. Piper nigrum (black pepper) is documented as susceptible to P. capsici, whereas its close relative Piper flaviflorum is known to be resistant. However, the molecular mechanism underlying the resistance of P. flaviflorum remains obscure. Here we conducted a comparative transcriptome and metabolome analysis between P. flaviflorum and P. nigrum upon P. capsici infection, and found substantial differences in their gene expression profiles, with altered genes being significantly enriched in terms relating to plant-pathogen interaction, phytohormone signal transduction, and secondary metabolic pathways, including phenylpropanoid biosynthesis. Further metabolome analysis revealed the resistant P. flaviflorum to have a high background endogenous ABA reservoir and time-course-dependent accumulation of ABA and SA upon P. capsici inoculation, while the susceptible P. nigrum had a high background endogenous IAA reservoir and time-course-dependent accumulation of JA-Ile, the active form of JA. Investigation of the phenylpropanoid biosynthesis metabolome further indicated the resistant P. flaviflorum to have more accumulation of lignin precursors than the susceptible P. nigrum, resulting in a higher accumulation after inoculation. This study provides an overall characterization of biologically important pathways underlying the resistance of P. flaviflorum, which theoretically explain the advantage of using this species as rootstock for the management of oomycete pathogen in black pepper production.